PERCERAIAN DENGAN ALASAN EKONOMI PERSPEKTIF MAQASHID SYARIAH - Fenni Febiana (Prodi Ilmu Hukum Fakultas Hukum Universitas Muhammadiyah Riau, 2018)
Economic (livelihood) is very needed in household life if we dismantle further economic (livelihood) is not everything, but if not given a complete living could trigger a number of serious problems and can cause considerable fatal riots in married life that divorce. divorce on economic grounds occupy numbers soar element is causing the divorce for economic reasons has increased the numbers are quite significant. In this article, the author tries to reassess the divorce for economic reasons to use sharia maqashid Overview to see the light of the problems of divorce on the grounds of the economy